Rare Earth Elements Emerging Advances, Technology Utilization, and Resource Procurement - Aide, Michael T. (IntechOpen, 2023)
Rare Earth Elements - Emerging Advances, Technology Utilization, and Resource Procurement illustrates the global interest in rare earth elements. The section on "Emerging Advances and Technology" presents research on the usage of rare earth elements in emerging technologies involving medicine, digital technology, mineral processing, and chemistry. The section on "Utilization and Resource Procurement" focuses on the global issues of pollution because of rare earth mining. The research presented underlies the rapid development of emerging technologies that require rare earth elements and the social issues that arise because of these technologies.